1986
DOI: 10.1152/ajpheart.1986.250.3.h509
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in hyperemic response of coronary blood flow in microembolization

Abstract: To investigate the pathophysiology of acute embolization of small coronary vessels and the role of adenosine in this abnormality, regional coronary blood flow (CBF), coronary vascular resistance, arteriovenous O2 difference, lactate extraction ratio, and adenosine release were studied in 39 anesthetized open-chest dogs after acute coronary embolization with microspheres of three different diameters (15 +/- 1, 94 +/- 8, and 293 +/- 23 microns). In 16 dogs, the left anterior descending coronary artery was emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 0 publications
2
98
1
3
Order By: Relevance
“…[1][2][3] Using an experimental model of coronary microembolization, 4 we have demonstrated that progressive myocardial contractile dysfunction develops within hours after an initial rapid recovery from the immediate microembolization-induced ischemic dysfunction. The present experiments confirmed this progressive myocardial dysfunction, and eventual full recovery was observed after 5 to 6 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Using an experimental model of coronary microembolization, 4 we have demonstrated that progressive myocardial contractile dysfunction develops within hours after an initial rapid recovery from the immediate microembolization-induced ischemic dysfunction. The present experiments confirmed this progressive myocardial dysfunction, and eventual full recovery was observed after 5 to 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Using an experimental model of coronary microembolization, 4 we have demonstrated that after a rapid (ie, minutes) recovery from the immediate microembolizationinduced ischemic dysfunction, a progressive (ie, hours) contractile dysfunction develops in the presence of unchanged regional myocardial blood flow. 5 Such perfusion-contraction mismatch was associated with a local inflammatory response characterized by leukocyte infiltration.…”
mentioning
confidence: 99%
“…10,11 This phenomenon seems to be due to adenosine-induced hyperemia of the myocardium surrounding the embolized microregions. 12 This interpretation is further supported by a study reporting that patients who experienced a prolonged hyperemic response after a percutaneous intervention had higher creatine phosphokinase values than patients without hyperemia.…”
Section: Determinants Of Impaired Cfvr After Angioplastymentioning
confidence: 99%
“…The high incidence of an impaired CFVR was due to an elevated baseline APV after PCI. Hori et al 30,31 showed that coronary microembolization increased baseline APV by release of adenosine in anesthetized dogs. Herrmann et al 2 reported an association of a periprocedural enzyme elevation with increased baseline APV and a reduced CFVR after stenting in patients with stable angina pectoris.…”
Section: Microembolization and Cfvrmentioning
confidence: 99%
“…Whereas we have focused on patients with chronic stable angina undergoing elective PCI, patients in the PROTECT-TIMI 30 trial had acute coronary syndromes with prior microembolization and subsequent release of adenosine, as well as thrombogenic and vasoconstrictor substances that may have confounded the assessment of coronary reserve. 30,31,40 …”
Section: Study Limitationsmentioning
confidence: 99%